1966
DOI: 10.1002/pol.1966.150040415
|View full text |Cite
|
Sign up to set email alerts
|

Studies on some radical transfer reactions. Part I. Hydrogen atom abstraction from some organic substrates by ȮH radicals

Abstract: Polymerization of methyl methacrylate was carried out in aqueous and nonaqueous media in the presence of some sulfonated and carboxylic organic compounds, hydroxyl radicals generated from hydrogen peroxide being used as initiators of polymerization. The occurrence of radical transfer reactions by way of hydrogen atom abstraction from the organic substrates by the ȮH radicals was demonstrated by the detection of sulfonate and carboxyl endgroups in the respective polymers. It was found that the radical transfer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1967
1967
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…When polymerization occurs in a solvent with a low chain transfer rate (e.g., tert -butanol, water, benzene), a polymer with a high molecular weight is formed. Mitra et al found that radical transfer reactions by way of hydrogen atom abstraction from the organic substrates by the OH ▪ radicals were more favoured in aqueous media than in non-aqueous systems [55]. This information can be of key importance when working with eutectic systems containing water.…”
Section: The Role Of Deep Eutectic Solvents In the Synthesis Of Pomentioning
confidence: 99%
“…When polymerization occurs in a solvent with a low chain transfer rate (e.g., tert -butanol, water, benzene), a polymer with a high molecular weight is formed. Mitra et al found that radical transfer reactions by way of hydrogen atom abstraction from the organic substrates by the OH ▪ radicals were more favoured in aqueous media than in non-aqueous systems [55]. This information can be of key importance when working with eutectic systems containing water.…”
Section: The Role Of Deep Eutectic Solvents In the Synthesis Of Pomentioning
confidence: 99%